Clinical scoring approach for detection of histiocytic necrotising lymphadenitis in adults. Issue 1 (16th December 2021) - Wang, Ning; Zhu, Yingying; Zhang, Jiaojiao; Pan, Shuming; Wang, Hairong
Abstract: Background: Histiocytic necrotising lymphadenitis (HNL) is rare and can be easily ignored. Aims: To summarise the characteristics of HNL and find a simple scoring approach to detect HNL in adult patients. Methods: Adult patients with lymphadenopathy diagnosed by lymph node biopsy were enrolled. Chi‐squared test and t ‐test were used to determine the significant variables. The cut‐off values and scores assigned to each factor were performed by receiver operating characteristic (ROC) curves and coefficients in the logistic regression respectively. The performance of the scoring system was evaluated by ROC curves. Results: There were 32 HNL cases and 1162 other cases in the present study. These features, including age, the frequency of presentations of fever, cervical and painful lymph nodes, decrease of white blood cells (WBC), ratio of neutrophil to WBC (N ratio) and elevated lactate dehydrogenase (LDH), were different between patients with HNL and other diseases. Based on the multivariate analysis, the scoring approach was defined as follows: score = 3 (fever) + 2 (cervical lymphadenopathy) + 2 (decreased WBC) + 1 (decreased N ratio) + 2 (elevated LDH). The cut‐off was score 4. This approach performed will detect HNL with an area under the curve of 0.889. Conclusion: The present study suggests that the novel scoring approach we put forward might be useful to detect HNL in adult patients though further studies are needed.